Formation of Hydroxyl Groups at Calcium-Silicate-Hydrate (C-S-H): Coexistence of Ca–OH and Si–OH on Wollastonite(001) - Sanna, Simone; Schmidt, Wolf Gero; Thissen, Peter (The Journal of Physical Chemistry C)

Rashba splitting and relativistic energy shifts in In/Si(111) nanowires - Gerstmann, Uwe; Vollmers, N. J.; Lücke, A.; Babilon, M.; Schmidt, Wolf Gero (Physical Review B)

IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Temperature dependent LiNbO3(0001): Surface reconstruction and surface charge - Sanna, S.; Hölscher, R.; Schmidt, Wolf Gero (Applied Surface Science)

Unraveling theLiNbO3X-cut surface by atomic force microscopy and density functional theory - Sanna, S.; Schmidt, Wolf Gero; Rode, S.; Klassen, S.; Kühnle, A. (Physical Review B)

Lithium niobate dielectric function and second-order polarizability tensor from massively parallel ab initio calculations - Riefer, Arthur; Rohrmüller, Martin; Landmann, Marc; Sanna, Simone; Rauls, Eva; Vollmers, Nora Jenny; Hölscher, Rebecca; Witte, Matthias; Li, Yanlu; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (High Performance Computing in Science and Engineering ‘13)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe–Salpeter equation yield a dielectric function for the stoichiometric material that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are at least partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that self-energy effects improve the agreement between experiment and theory. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular for the 21 and 31 tensor components, further improving the agreement with measured data.

Geometrical and optical benchmarking of copper guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory† - Jesser, Anton; Rohrmüller, Martin; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Friggeet al.Reply: - Frigge, T.; Wall, S.; Krenzer, B.; Wippermann, St.; Sanna, S.; Klasing, F.; Hanisch-Blicharski, A.; Kammler, M.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review Letters)

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

Charge compensation by long-period reconstruction in strongly polar lithium niobate surfaces - Sanna, S.; Rode, S.; Hölscher, R.; Klassen, S.; Marutschke, C.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Adsorption of PTCDA on NaCl(100) and KCl(100) - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Monolayer Doping via Phosphonic Acid Grafting on Silicon: Microscopic Insight from Infrared Spectroscopy and Density Functional Theory Calculations - Longo, Roberto C.; Cho, Kyeongjae; Schmidt, Wolf Gero; Chabal, Yves J.; Thissen, Peter (Advanced Functional Materials)

Optical response of stoichiometric and congruent lithium niobate from first-principles calculations - Riefer, Arthur; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe-Salpeter equation for the stoichiometric material yield a dielectric function that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are, at least, partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that the inclusion of self-energy effects in the nonlinear optical response leads to a better agreement with experiments. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular, for the 21 and 31 tensor components, further improving the agreement between experiments and theory.

Structural variety of 5-fluoroarene-2-aminopyrimidine in comparison to 2-aminopyrimidine silver(i) coordination polymers: progress report and overview - Eberhard, Jens; Stoll, Ion; Brockhinke, Regina; Neumann, Beate; Stammler, Hans-Georg; Riefer, Arthur; Rauls, Eva; Schmidt, Wolf Gero; Mattay, Jochen (CrystEngComm)

Bis-μ-oxo and μ-η2:η2-peroxo dicopper complexes studied within (time-dependent) density-functional and many-body perturbation theory - Rohrmüller, M.; Herres-Pawlis, S.; Witte, M.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic Structure of Interface States in Silicon Heterojunction Solar Cells - George, B. M.; Behrends, J.; Schnegg, A.; Schulze, T. F.; Fehr, M.; Korte, L.; Rech, B.; Lips, K.; Rohrmüller, M.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, U. (Physical Review Letters)

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

Vibrational Fingerprints of LiNbO3-LiTaO3Mixed Crystals - Sanna, Simone; Riefer, A.; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Rüsing, Michael; Widhalm, A.; Zrenner, Artur (Ferroelectrics)
Atomistic simulations in the framework of the density functional theory have been used to model morphologic and vibrational properties of lithium niobate–lithium tantalate mixed crystals as a function of the [Nb]/[Ta] ratio. Structural parameters such as the crystal volume and the lattice parameters a and c vary roughly linearly from LiTaO3 to LiNbO3, showing only minor deviations from the Vegard behavior. Our ab initio calculations demonstrate that the TO1, TO2 and TO4 vibrational modes become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. Furthermore, the investigated zone center A1 -TO phonon modes are characterized by a pronounced stoichiometry dependence. Frequency shifts as large as 30 cm−1 are expected as the [Nb]/[Ta] ratio grows from 0 to 1. Therefore, spectroscopic techniques sensitive to the A1 modes (such as Raman spectroscopy), can be employed for a direct and non-destructive determination of the crystal composition.
Keywords: Ferroelectrics; vibrational properties; LiNbO3; LiTaO3; mixed crystals

Transition energies and direct-indirect band gap crossing in zinc-blende AlxGa1−xN - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schupp, Thorsten; As, Donat J.; Feneberg, Martin; Goldhahn, Rüdiger (Physical Review B)

Substrate Induced Thermal Decomposition of Perfluoro-Pentacene Thin Films on the Coinage Metals - Schmidt, Christian; Breuer, Tobias; Wippermann, Stefan; Schmidt, Wolf Gero; Witte, Gregor (The Journal of Physical Chemistry C)

Atomistic Picture of Charge Density Wave Formation at Surfaces - Wall, Simone; Krenzer, Boris; Wippermann, Stefan; Sanna, Simone; Klasing, Friedrich; Hanisch-Blicharski, Anja; Kammler, Martin; Schmidt, Wolf Gero; Horn-von Hoegen, Michael (Physical Review Letters)

Ferroelectric phase transition in LiNbO3: Insights from molecular dynamics - Sanna, S.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Linear and nonlinear optical response of LiNbO3 calculated from first principles - Riefer, Arthur; Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Polarization-dependent methanol adsorption on lithium niobate Z-cut surfaces - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Physical Review B)

Atomic-resolution imaging of the polar (0001¯) surface of LiNbO3in aqueous solution by frequency modulation atomic force microscopy - Rode, S.; Hölscher, R.; Sanna, S.; Klassen, S.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Fingerprints of order and disorder in the electronic and optical properties of crystalline and amorphous TiO2 - Landmann, M.; Köhler, T.; Köppen, S.; Rauls, E.; Frauenheim, T.; Schmidt, Wolf Gero (Physical Review B)

Activation of Surface Hydroxyl Groups by Modification of H-Terminated Si(111) Surfaces - Thissen, Peter; Peixoto, Tatiana; Longo, Roberto C.; Peng, Weina; Schmidt, Wolf Gero; Cho, Kyeongjae; Chabal, Yves J. (Journal of the American Chemical Society)

Interplay between metal-free phthalocyanine molecules and Au(110) substrates - Rauls, E.; Schmidt, Wolf Gero; Pertram, T.; Wandelt, K. (Surface Science)

The electronic structure and optical response of rutile, anatase and brookite TiO2 - Landmann, M; Rauls, E; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

2-Aminopyrimidine-silver(I) based organic semiconductors: Electronic structure and optical response - Riefer, A.; Rauls, E.; Schmidt, Wolf Gero; Eberhard, J.; Stoll, I.; Mattay, J. (Physical Review B)

pH-dependent structure and energetics of H2O/MgO(100) - Thissen, Peter; Thissen, Vera; Wippermann, Stefan; Chabal, Yves J.; Grundmeier, Guido; Schmidt, Wolf Gero (Surface Science)

Adsorption of OH and H at the LiNbO3(0001) surface - Hölscher, R.; Sanna, S.; Schmidt, Wolf Gero (physica status solidi (c))

In-Si(111)(4 × 1)/(8 × 2) nanowires: Electron transport, entropy, and metal-insulator transition - Schmidt, Wolf Gero; Wippermann, S.; Sanna, S.; Babilon, M.; Vollmers, N. J.; Gerstmann, Uwe (physica status solidi (b))

First-principles and empirical potential simulation study of intrinsic and carbon-related defects in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Schmidt, Wolf Gero; Rauls, E.; Lindner, Jörg K. N. (physica status solidi (c))
Results of atomistic simulations aimed at understanding precipitation of the highly attractive wide band gap semiconductor material silicon carbide in silicon are presented. The study involves a systematic investigation of intrinsic and carbon-related defects as well as defect combinations and defect migration by both, quantummechanical first-principles as well as empirical potential methods. Comparing formation and activation energies, ground-state structures of defects and defect combinations as well as energetically favorable agglomeration of defects are predicted. Moreover, accurate ab initio calculations unveil limitations of the analytical method based on a Tersoff-like bond order potential. A work-around is proposed in order to subsequently apply the highly efficient technique on large structures not accessible by first-principles methods. The outcome of both types of simulation provides a basic microscopic understanding of defect formation and structural evolution particularly at non-equilibrium conditions strongly deviated from the ground state as commonly found in SiC growth processes. A possible precipitation mechanism, which conforms well to experimental findings and clarifies contradictory views present in the literature is outlined.

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)

Influence of Na adsorption on the quantum conductance and metal-insulator transition of the In-Si(111)(4×1)–(8×2) nanowire array - Schmidt, Wolf Gero; Babilon, M.; Thierfelder, C.; Sanna, S.; Wippermann, S. (Physical Review B)

Group-VII point defects in ZnSe - dos Santos, L. S.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Preserving Charge and Oxidation State of Au(III) Ions in an Agent-Functionalized Nanocrystal Model System - Müllegger, Stefan; Schöfberger, Wolfgang; Rashidi, Mohammad; Lengauer, Thomas; Klappenberger, Florian; Diller, Katharina; Kara, Kamuran; Barth, Johannes V.; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold (ACS Nano)

Electrically Detected Electron-Spin-Echo Envelope Modulation: A Highly Sensitive Technique for Resolving Complex Interface Structures - Hoehne, Felix; Lu, Jinming; Stegner, Andre R.; Stutzmann, Martin; Brandt, Martin S.; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Letters)

Microscopic structure and energy transfer of vacancy-related defect pairs with Erbium in wide-gap semiconductors - Konopka, A.; Greulich-Weber, S.; Dierolf, V.; Jiang, H.X.; Gerstmann, Uwe; Rauls, E.; Sanna, S.; Schmidt, Wolf Gero (Optical Materials)

Band offsets in cubic GaN/AlN superlattices - Mietze, C.; Landmann, M.; Rauls, E.; Machhadani, H.; Sakr, S.; Tchernycheva, M.; Julien, F. H.; Schmidt, Wolf Gero; Lischka, K.; As, Donat Josef (Physical Review B)

Driving forces for the adsorption of cyclopentene on InP(001) - Favero, P.P.; Ferraz, A.C.; Schmidt, Wolf Gero; Miotto, R. (Surface Science)

Asymmetric saddling of single porphyrin molecules on Au(111) - Müllegger, S.; Rashidi, M.; Lengauer, T.; Rauls, E.; Schmidt, Wolf Gero; Knör, G.; Schöfberger, W.; Koch, R. (Physical Review B)

Methane adsorption on graphene from first principles including dispersion interaction - Thierfelder, C.; Witte, M.; Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, G.; Hahn, W.; Widhalm, A.; Zrenner, A.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Combined ab initio and classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Barium titanate ground- and excited-state properties from first-principles calculations - Sanna, S.; Thierfelder, C.; Wippermann, S.; Sinha, T. P.; Schmidt, Wolf Gero (Physical Review B)

Localised Phonon Modes at LiNbO3(0001) Surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, Wolf Gero (Ferroelectrics)
The vibrational properties of the LiNbO3 (0001) surfaces have been investigated both from first principles and with Raman spectroscopy measurements. Firstly, the phonon modes of bulk and of the (0001) surface are calculated by means of the density functional theory. Our calculations reveal the existence of localised vibrational modes both at the positive and at the negative surface. The surface vibrations are found at energies above and within the bulk bands. Phonon modes localised at the positive and at the negative surface differ substantially. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces have been measured. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. The calculated and measured frequencies are in agreement within the error of the method.

Do we know the band gap of lithium niobate? - Thierfelder, Christian; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physica Status Solidi C)
Given the vast range of lithium niobate (LiNbO3) applications, the knowledge about its electronic and optical properties is surprisingly limited. The direct band gap of 3.7 eV for the ferroelectric phase – frequently cited in the literature – is concluded from optical experiments. Recent theoretical investigations show that the electronic band‐structure and optical properties are very sensitive to quasiparticle and electron‐hole attraction effects, which were included using the GW approximation for the electron self‐energy and the Bethe‐Salpeter equation respectively, both based on a model screening function. The calculated fundamental gap was found to be at least 1 eV larger than the experimental value. To resolve this discrepancy we performed first‐principles GW calculations for lithium niobate using the full‐potential linearized augmented plane‐wave (FLAPW) method. Thereby we use the parameter‐free random phase approximation for a realistic description of the nonlocal and energydependent screening. This leads to a band gap of about 4.7 (4.2) eV for ferro(para)‐electric lithium niobate.

Ab initiog-tensor calculation for paramagnetic surface states: hydrogen adsorption at Si surfaces - Gerstmann, Uwe; Rohrmüller, M.; Mauri, F.; Schmidt, Wolf Gero (physica status solidi (c))